The analysis of migration inflows and outflows in interrelation with the budget - Veynbender, T. L. (Opción, 2019)
In the article the review of migration flows in Russia, in particular in the Tyumen region is carried out through descriptive research design method. Relationship of cause and effect of the inflow of migrants to the Tyumen region is revealed. The conclusions and offers which are contained in the article represent a certain contribution to a research of problems of regional migration. Results of a research are received on the basis of processing of theoretical and statistical material during 1990-2017 in the migration sphere of the Russian Federation that has allowed to carry out the analysis